(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the theoretical and practical foundations of improving employee labor productivity in modern enterprises. The study analyzes labor productivity as an important economic category directly connected with organizational efficiency, technological development, and human-capital management. Particular attention is devoted to labor organization systems, process-based management, digital technologies, Lean production, team-based management, and ergonomic optimization. The research applies analytical, comparative, and systemic approaches to evaluate the influence of modern management models on production efficiency and labor performance. Research findings demonstrate that integrated labor-management systems significantly increase productivity, reduce operational losses, improve resource utilization, and strengthen enterprise competitiveness. The article further explores the role of digital transformation and human-capital development in increasing labor efficiency under conditions of economic modernization.